Risk factors and outcomes of intraoperative hypothermia in neonatal and infant patients undergoing general anesthesia and surgery - Zhao, Jialian; Le, Zhenkai; Chu, Lihua; Gao, Yi; Zhang, Manqing; Fan, Jiabin; Ma, Daqing; Hu, Yaoqin; Lai, Dengming (Frontiers in Pediatrics, 2023)
Abstract Objective：The incidence of intraoperative hypothermia still remains high in pediatric patients during anesthesia and surgery even though core body temperature monitoring and warming system were greatly improved these years. We analyzed risk factors and outcomes of intraoperative hypothermia in neonates and infants undergoing general anesthesia and surgery. Methods：The data of the incidence of intraoperative hypothermia, other clinical characteristics and outcomes from electronic records of 1,091 patients (501 neonates, and 590 infants between 28 days and 1year old), who received general anesthesia and surgery, were harvested and analyzed. Intraoperative hypothermia was defined as core temperature below 36°C during surgery. Results：The incidence of intraoperative hypothermia in neonates was 82.83%, which was extremely higher than infants (38.31%, p<0.001); the same as the lowest body temperature (35.05±0.69°C vs. 35.40±0.68°C, p<0.001) and the hypothermia duration (86.6±44.5 minutes vs. 75.0±52.4 minutes, p<0.001). Intraoperative hypothermia was associated with prolonged PACU, ICU, hospital stay, postoperative bleeding and transfusion in either age group. Intraoperative hypothermia in infants was also related with prolonged postoperative extubation time and surgical site infection. After univariate and multivariate analysis, the age (OR=0.902,p<0.001), weight (OR=0.480, p=0.013), prematurity (OR=2.793, p=0.036), surgery time more than 60 minutes (OR=3.743, p<0.001), pre-warming(OR=0.081, P<0.001), fluid received＞20ml/kg (OR=2.938, P=0.004), emergency surgery (OR=2.142, p=0.019) were associated with hypothermia in neonates. Similar to neonates, age (OR= 0.991, p<0.001), weight (OR=0.783, p=0.019), surgery time > 60minutes (OR=2.140, p=0.017), pre-warming (OR=0.017, p<0.001) and fluid received＞20ml/kg (OR=3.074, P=0.001) were relevant factors to intraoperative hypothermia in infants along with the ASA grade (OR=4.135, p<0.001). Conclusion：The incidence of intraoperative hypothermia was still high especially in neonates with a few detrimental complications. Neonates and infants each have their own different risk factors associated with intraoperative hypothermia but younger age, lower weight, long surgery time, more fluid received and without prewarming management were the common risk factors. Key words: Intraoperative hypothermia, perioperative hypothermia, neonate, infant, pre-warming, thermal management